Effects of 6 months of abatacept treatment on aortic stiffness in patients with rheumatoid arthritis - Mathieu S (Dove Medical Press, 2013)
Sylvain Mathieu,1,2 Marion Couderc,1,2 Baptiste Glace,1,2 Bruno Pereira,2,3 Anne Tournadre,1,2 Jean-Jacques Dubost,1,2 Martin Soubrier1,21Department of Rheumatology, Gabriel-Montpied Hospital, 2Faculty of Medicine, University Clermont 1, 3Délégation de la Recherche Clinique, Gabriel-Montpied Hospital, Clermont-Ferrand, FranceBackground: Systemic inflammation plays an important role in the increased cardiac risk observed in rheumatoid arthritis (RA). Effective control of inflammation and disease activity may be of benefit in reducing cardiovascular risk in RA patients.Objective: Our study was conducted in patients with active RA to investigate the effects of 24-week abatacept treatment on aortic stiffness measured by pulse wave velocity (PWV).Results: The study included 21 patients, of whom 17 were females, with a mean age of 65.2±13.7 years. Ten patients had positive rheumatoid factors, 16 positive anti-citrullinated protein antibodies, and 19 presented an erosive form of RA. Sixteen patients were nonresponders to anti-tumor necrosis factor-alpha treatments. After 6 months of abatacept treatment, there was a significant increase in PWV levels (9.8±2.9 versus 8.5±3.9 m/second; P=0.02). A nonsignificant increase in total cholesterol and low-density lipoprotein cholesterol was observed. There was also a significant increase in high-density lipoprotein cholesterol levels, which led to a nonsignificant decrease in atherogenic index. The improvement in disease activity was significant, and there was a decrease of systemic inflammatory parameters, but without reaching statistical significancy. Changes in PWV were significantly correlated with changes in Disease Activity Score on 28 joints based on erythrocyte sedimentation rate (r=0.46; P=0.035) and in high-density lipoprotein cholesterol (r=-0.38; P=0.046). No correlation was observed with changes in C-reactive protein and in other parameters of lipid profile or in steroid dose.Conclusion: The worsening of aortic stiffness found after 6 months of abatacept therapy might be due to an insufficient decrease in systemic inflammation.Keywords: arterial stiffness, cardiovascular risk markers, systemic inflammation, atherogenic index